2018
DOI: 10.1111/jdv.14999
|View full text |Cite
|
Sign up to set email alerts
|

High volume of polysorbate‐containing (Tween® 80) solutions induces false‐positive results in intradermal test

Abstract: Different volumes of polysorbate-containing solutions, all recommended by manufacturers for intradermal tests, may significantly influence test results. The study shows that a polysorbate 80 used at 0.005% in solvents for intradermal test to provide a better bioavailability of allergens produces false-positive reactivity in a surprising and a hitherto unknown 77% if the 0.05 mL volume is injected. It is, therefore, mandatory to strictly adhere to an intradermal test volume of 0.02 mL as only then falsifying ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A systematic review identified 21 studies (all case reports/series) out of 548 citations (excluding duplicates) that described skin testing (skin prick or intradermal) to PEG of any molecular weight and/or polysorbate 80, in which control subjects were also tested. 15,16,[96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] A positive case was defined as any method of skin testing performed with PEG or polysorbate concentration in which the authors deemed the test positive for identification of a wheal and/or flare, without any specific or uniform threshold reported. For PEG, there were 15 reports detailing skin testing to varying agents and concentrations.…”
Section: Rationale Systematic Review and Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review identified 21 studies (all case reports/series) out of 548 citations (excluding duplicates) that described skin testing (skin prick or intradermal) to PEG of any molecular weight and/or polysorbate 80, in which control subjects were also tested. 15,16,[96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] A positive case was defined as any method of skin testing performed with PEG or polysorbate concentration in which the authors deemed the test positive for identification of a wheal and/or flare, without any specific or uniform threshold reported. For PEG, there were 15 reports detailing skin testing to varying agents and concentrations.…”
Section: Rationale Systematic Review and Meta-analysismentioning
confidence: 99%
“…There were 6 reports detailing 7 total patients with suspected allergy to polysorbate that had skin testing (no false positives, and 57 controls tested that were nonreactive). [109][110][111][112][113][114] The same systematic review identified no studies that investigated vaccine or excipient testing compared with negative controls in individuals with a known or suspected allergic reaction of any severity to a SARS-CoV-2 vaccine. However, 4 case reports (without controls) were identified describing testing with SARS-CoV-2 mRNA vaccine or PEG/polysorbate in persons with reported severe allergic reactions to the vaccine, and vaccine testing in negative controls to establish a nonirritating testing concentration.…”
Section: Rationale Systematic Review and Meta-analysismentioning
confidence: 99%
“…IDT with PEG carries a risk of systemic reactions. Restivo et al [43] recommend that only a PEG 0.01% dilution should be used for IDT in SPT-negative patients. Moreover, they advise avoiding IDT in high-risk patients because of the possibility of systemic reactions even with a negative skin test [43].…”
Section: Skin Testsmentioning
confidence: 99%
“…A prick test can be performed for diagnosis [ 13 ]. False-positive reactions are possible in the intradermal test, which can be seen in particular when applying volumes > 0.02 ml [ 14 ].…”
Section: Polysorbate 80 (E 433)mentioning
confidence: 99%